ENTREPRENEUR INTENTION: EDUCATION KNOWLEDGE, ATTITUDE ENTREPRENEUR AND SELF-EFFICACY - Denis Fidita Karya; Rizki Amalia Elfita (Universitas 17 Agustus 1945 Surabaya, 2022)
The problem of unemployment is also a crucial problem in Indonesia. Currently, the number of unemployed in Indonesia reaches 6.1 million people, where the largest unemployment rate occurs in the young group aged 20-29 years (World Employment and Social Outlook (WESO), 2022). The purpose of this study is to see whether entrepreneurial knowledge and attitude toward entrepreneurship can affect self-efficacy and entrepreneurial intention. Method research using quantitative methods with sampling techniques sampling purposive sampling. The questionnaires were distributed online via google form distributed to 200 respondents. The analysis can be in this study using Partial Least Square (PLS). Research result: There is a significant influence between entrepreneurial knowledge, attitude toward entrepreneurs on self-efficacy, and entrepreneurial intention. Keyword: Entrepreneur Intention, Attitude Entrepreneurship, Education Knowledge